Managing Gastrointestinal Complications of Diabetes - Sellin, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
An ideal clinical handbook for medical professionals that regularly treat patients with diabetes and comorbid gastrointestinal complications. The concise format provides evidence-based content with a targeted emphasis on diagnosis, as up to 75% of patients visiting diabetes clinics report significant gastrointestinal symptoms. Includes guidelines for complication prevention, treatment, and long-term disease management.
Chapter 1 Introduction -- Chapter 2 Esophageal disease in diabetes mellitus -- Chapter 3 -- Diabetic gastroparesis -- Chapter 4 -- Small intestine and colon complications patients with diabetes -- Chapter 5 Non-alcoholic fatty liver disease -- Chapter 6 -- Non-alcoholic fatty liver disease and hepatocellular carcinoma -- Chapter 7 Diabetes, specific heptobiliary disease, and treatment -- Chapter 8 Diabetes, cirrhosis, and liver transplantation -- Chapter 9 Diabetes and the exocrine pancreas.
Keywords: Medicine; General practice (Medicine).; Diabetes; Endocrinology; Gastroenterology; Primary care (Medicine).; Medicine & Public Health; Diabetes; Gastroenterology; General Practice / Family Medicine; Primary Care Medicine; Endocrinology